Violence in the home multidisciplinary perspectives - Kurst-Swanger, Karel, 1961-; Petcosky, Jacqueline L., 1962- (Oxford : Oxford University Press, 2003)
Violence in the home is one of the most damaging and widespread of social problems. This book reviews the most current theoretical explanations of family violence and then links theory to practice.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Family violence; Family violence -- United States; Family violence -- Prevention